RENCANA KEWIRAUSAHAAN DENGAN PRINSIP MUDHARABAH: PISANG KRISPI - Kusuma, Aditya Agil Ghazi; Mustauda, Amy; Prasetyo, Zidane Rizky; Hidayah, Fadhilah Nur; Fathoni, Naufal Ilham; Jati, Henggar Kusuma (Forum Bisnis Kewirausahaan, 2025)
This article aims to create an entrepreneurial plan by utilizing easily accessible materials, specifically bananas, which are affordable and based on the mudharabah principle. The business plan involves a product called Pisang Krispi, which are fried bananas topped with various toppings, sold through a pre-order system via social media platforms such as WhatsApp, Instagram, and others. The initial capital for this businessis IDR 2,200,000, with monthly operational costs amounting to IDR 2,500,000, a selling price of IDR 5,000 per pack, and a monthly revenue of IDR 7,500,000 if 50 packs of bananas are sold.